Article 6 of the Paris agreement piloting for enhanced readiness. (Metro Manila, Philippines Asian Development Bank, 2018)
This publication outlines the rationale for and benefits of piloting activities for Article 6 of the Paris Agreement.It emphasizes the need for testing alternate approaches and sharing of experiences. Article 6 provides for voluntary international cooperation that may facilitate the use of market-based approaches to help countries achieve their nationally determined contributions and enable greater gains. Pilot activities in developing member countries of the Asian Development Bank can help Asia and the Pacific develop capacity, readiness, and awareness on using Article 6 and participating in international carbon markets.
Keywords: Environmental policy -- International cooperation; Climatic change mitigation; Electronic books